Materials response to glancing incidence femtosecond laser ablation. (1st February 2017) - Echlin, McLean P.; Titus, Michael S.; Straw, Marcus; Gumbsch, Peter; Pollock, Tresa M.
Abstract: A femtosecond Ti:sapphire laser was used to ablate samples of copper, strontium titanate (STO), a nickel alloy René 88DT (R88), {111}-oriented single crystal silicon, and gallium nitride (GaN) in situ in a focused ion beam scanning electron microscope (FIB-SEM). The laser beam was scanned parallel to the specimen surface, which resulted in laser ablation using the tail of the Gaussian beam distribution, near the ablation threshold for each of the materials. Transmission electron microscopy (TEM) and electron backscatter diffraction (EBSD) were utilized to investigate damage in the bulk and at the surface of the laser ablated samples in cross-sections that were extracted by FIB-SEM. In contrast to normal incidence, post-ablation damage in the glancing incidence configuration was extremely limited across a wide range of laser pulse energies. Elevated dislocation densities were observed within 150–200 nm of the ablated surface in the Cu, STO, and R88 samples. An amorphized Si layer as thin as 30–50 nm was observed with no dislocations near the surface or in the bulk. Gallium nitride exhibited exceptional damage resistance to femtosecond laser irradiation, whereby no laser-induced dislocations or amorphization near the ablated surface was observed. For materials where there is surface damage following laser ablation, we show that a subsequent machining step with a Ga + FIB beam located in the same chamber can remove this damage in a short period of time. Graphical abstract: Image 1